Diseño de un banco de pruebas para cilindros hidráulicos, motores hidráulicos y bloques de válvulas para la empresa Hidráulica Industrial JC SAS (2022)
The purpose of the project is to reduce the novelties of guarantees in the references of single-acting and double-acting cylinders, valve blocks for elevators and hydraulic motors marketed by the company HIDRAULICA INDUSTRIAL JC SAS that present a greater number of reports. The design of a mixed test bench is carried out taking into account the specifications requested by the company when carrying out the tests on its equipment before its commercialization or after some maintenance procedure in order to know the current state of operation in the where the device in question is located.